Fundamental electronic and magnetic interactions in the cage compounds RT2Zn20 (R = Y, Gd, Yb, T = Fe, Co) - Baez, Michael Cabrera (2017)
The electronic correlations originated from the Coulomb interactions between electrons play a fundamental role in the establishment of the physical properties of a wide range of materials. For the case of weak correlations, the material can be described within a simplied non-interacting point of view, as in the case of standard metals. Unexpected and intriguing properties are revealed when strong correlations are involved, due to a large number of degrees of freedom in the electronic correlations. As a result of this electronic correlation, it is possible to go from conventional forms of magnetism, passing through superconducting systems and reaching heavy fermion behavior. Members within a single family of compounds can provide all those very dierent ground states, and the opportunity to study and try to understand some of the electronic and magnetic fundamental interactions involved. This thesis is a result of exploring these dierent behaviors that arise from electron-electron correlations, specically in the family of cage compounds RT2Zn20 (R=Y,Gd,Yb and T=Fe,Co). A detailed combination of quantitative macroscopic and microscopic descriptions of the electronic, thermodynamic and magnetic properties of some members of this family were developed. The rst part of this thesis presents a study on Gd3+- doped YCo2Zn20 single crystals (Y1..xGdxCo2Zn20: (0.002 . x 1.00) through a combination of temperature-dependent Electron Spin Resonance (ESR), heat capacity and dc magnetic susceptibility experiments, plus collaborative rst-principles Density Functional Theory (DFT) calculations. The combination of experimental and electronic structure data establish GdCo2Zn20 as a model Ruderman-Kittel-Kasuya-Yosida (RKKY) system by predicting a Curie-Weiss temperature C = ..1:2(2) K directly from microscopic parameters, in very good agreement with the bulk value from magnetization data. The second part involves an exploration of the unconventional ferromagnetic behaviors that have been found in GdFe2Zn20, which has a relatively high ferromagnetic ordering temperature (TC = 86 K) despite being a system with wide separation between Gd3+ ions in a matrix with strong electron-electron correlation. Taking into account those correlations and itinerant molecular eld eects, analysis of our ESR results indicate that the exchange interaction between the Gd3+ is processed via the d-type of electrons at the Fermi level and becomes an exchange interaction of covalent nature (J(0)fd < 0). Our results shows that the RKKY model cannot explain the ferromagnetic behavior of this compound, and a super-exchange-like mechanism is proposed for this magnetic interaction. Increasing a little bit the level of complexity, the third part of this thesis is on the tuning of the electronic properties of the heavy fermion compound YbFe2Zn20 by chemical substitution (Cd doping). With increasing amount of Cd, the hybridization between Yb 4f electrons and the conduction electrons is weakened, which should be accompanied by a valence shift of the Yb3+ due to the negative chemical pressure eect. The combined results demonstrate excellent complementarity between positive physical pressure and negative chemical pressure, and point to a rich playground for exploring the physics of strongly correlated electron systems. Finally, this thesis ends with a general set of conclusions of the explored quantum materials.